2005
DOI: 10.1111/j.1742-1241.2004.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological aspects of irritable bowel syndrome in Southeastern Anatolia: a stratified randomised community-based study

Abstract: Even though studies on the epidemiology of the irritable bowel syndrome (IBS) are increasing day by day, epidemiological data are still unknown in many regions. Our objective was to determine the IBS prevalence, factors associated with this prevalence and probable risk groups in Southeastern Anatolia. The total population in the target region is approximately 6 million. A total of 3000 people (1521 females and 1479 males) randomly selected by stratified cluster sampling were interviewed face-to-face by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
2
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
4
14
2
8
Order By: Relevance
“…In the logistic regression, a high income and few years of education were most closely associated with IBS, and we identified a small group of men with a particularly high prevalence of IBS; they had received only primary education but had a high income and they also had high distress and life events score. This is similar to the report from Turkey, where IBS was most common in respondents who were literate but had not been officially educated; such a position was considered to be particularly stressful 36 . It has also some similarity with Gwee’s 5 suggestion that increasing wealth in a developing country is accompanied by an increased chance of IBS.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the logistic regression, a high income and few years of education were most closely associated with IBS, and we identified a small group of men with a particularly high prevalence of IBS; they had received only primary education but had a high income and they also had high distress and life events score. This is similar to the report from Turkey, where IBS was most common in respondents who were literate but had not been officially educated; such a position was considered to be particularly stressful 36 . It has also some similarity with Gwee’s 5 suggestion that increasing wealth in a developing country is accompanied by an increased chance of IBS.…”
Section: Discussionsupporting
confidence: 84%
“…This is similar to the report from Turkey, where IBS was most common in respondents who were literate but had not been officially educated; such a position was considered to be particularly stressful. 36 It has also some similarity with GweeÕs 5 suggestion that increasing wealth in a developing country is accompanied by an increased chance of IBS. This might be related to increased stress, but we do not have data to comment on whether this is related to change in diet or lack of exposure to infection during childhood, but the latter seems unlikely in this group.…”
Section: Discussionsupporting
confidence: 56%
“…[29][30][31][32][33][34] However, we found that gender had no influence on IBS incidence in our study population. Higher socioeconomic status was a predictive factor for IBS diagnosis and deterioration in our study cohort.…”
Section: Discussioncontrasting
confidence: 57%
“…This study was done as door to door survey using random sampling. The prevalence of IBS in both the above community based study was not only much lower than that reported from the Western countries; but also much lower than community based studies from other Asian countries like Taiwan (22.1% by Rome II criteria),17 China (11.5% by Manning criteria),18 Singapore (8.6% by Rome II criteria),9 Malaysia (15.6% by Rome II criteria),19 Bangladesh (8.5% by Rome II criteria),20 Pakistan (14% by Rome II criteria),21 Turkey (10.2% by Rome II criteria),22 Korea (6.6% by Rome II criteria)23 and Japan (9.8% by Rome II criteria) 10…”
Section: Discussionmentioning
confidence: 99%